Special Spot Day Care Graduation in Watkins' Backyard - Watkins, Howard::::::::: (1983)
Front: ???, Kent Tracy, ?, Adam Watkins, Devon Bleile-Kratzer; Back: ??, Seth Tilley, Annie Tilley, David Tilley, Jake Tilley, Howard Watkins, Christine Watkins, Annie Bleile-Kratzer being held by Nancy Bleile-Kratzer, Jim Kratzer, Greg Wille holding Art Wille, Cathy Wille holding Maya Wille